PENGARUH HEAT MOISTURE TREATMENT PATI SAGU TERHADAP KARAKTERISTIK KIMIA STIK SARUT (PANGAN TRADISIONAL MALUKU) - Tetelepta, Gilian; Picauly, Priscillia (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
The purpose of this research was to determine the appropriate heat moisture treatment modified with different moisture contents to produce sarut stick. A completely randomized experimental design with native sago starch and different moisture content (24%, 27%, dan 30%) and 3 replications was applied in this research. The result show that the HMT treatment of 27% was found to be the right treatment with the highest levels namely water content 2,83%, ash content of 0,87%, protein content of 2,13%, fat content 8,11%, carbohydrate content 86,06% and crude fiber content 13,16%.